CD9, a tetraspan transmembrane protein, renders cells susceptible to canine distemper virus. - Löffler, S (1997)
Canine distemper virus (CDV), a lymphotropic and neurotropic negative-stranded RNA virus of the Morbillivirus genus, causes a life-threatening disease in several carnivores, including domestic dogs. To identify the cellular receptor(s) involved in the uptake of CDV by susceptible cells, we isolated a monoclonal antibody (MAb K41) which binds to the cell surface and inhibits the CDV infection of several cell lines from various species. Pretreatment of cells with MAb K41 reduces the number of infectious centers and the size of the syncytia. Using affinity chromatography with MAb K41, we purified from HeLa and Vero cell extracts a 26-kDa protein which contained the amino acid sequence TKDEPQRETLK of human CD9, a member of the tetraspan transmembrane or transmembrane 4 superfamily of cell surface proteins. Transfection of NIH 3T3 or MDBK cells with a CD9 expression plasmid rendered these cells permissive for viral infection and raised virus production by a factor of 10 to 100. The mechanism involved is still unclear, since we were unable to detect direct binding of CDV to CD9 by using immunoprecipitation and a virus overlay protein binding assay. These findings indicate that human CD9 and its homologs in other species are necessary factors for the uptake of CDV by target cells, the formation of syncytia, and the production of progeny virus.